PEMBERIAN PENYULUHAN DAN PENDAMPINGAN TENTANG PENGOLAHAN DANA DESA GUNA MENGHINDARI MALADMINISTRASI DAN KORUPSI - Meirza Aulia Chairani; Krista Yitawati; Angga Pramodya Pradhana (Universitas Merdeka Madiun, 2023)
The village is the smallest unit of government. Villages by the Village Law in the use of village funds must apply all funds properly and by their respective plots. However, many villages cannot apply the village funds provided by the local government in their development. Resulting in several actions that lead to Corruption and maladministration. So it is necessary to provide counseling and assistance regarding processing village funds to avoid maladministration and corruption. There needs to be internal and external supervision of the village government. The village government needs to carry out administrative accountability so that all villagers can be transparent about village funds, all residents know that all village funds can run well if the village apparatus commits criminal acts of corruption. The village government in implementing the APBDES must plan development in one year by the village funds issued by the local government. Therefore, counseling and legal guidance are needed to reduce maladministration and reduce criminal acts of corruption. Village governments need to implement the following Law Number 6 of 2014 concerning Villages.